PENGARUH REGULASI DAN KETERSEDIAAN ANGGARAN TERHADAP KINERJA PELAYANAN APARATUR SKPD DAN IMPLIKASINYA PADA KUALITAS PELAYANAN PUBLIK DI PROVINSI ACEH - Idris, Amiruddin; Konadi, Win (JURNAL KEBANGSAAN, 2012)
Human resource take the strategy position among the other resource in organization/institution. But in reality, there are still many organitations do not cosider the important thing of the human resource for organization sustainable. Therefore, many enterprises officers and viewed as the most important asset of organization. The improvement of the workers quality in many institution are hoped to be able in increasing the social service. The result of survey contemporary, showed that there are still many problems in Aceh province such as ; the weaknesses for the competativeness nationally. The management of institution (Good Govermence) is hot running well. The understanding of regulation and its implementation is still very limited. The quality of the goverment officer, and the process to develop the human resources in Aceh are not still running well. This research is focused on the impact of the regulation and the budget availability which able to increase the public service in five districts of Aceh province. The result of this research showed that a good regulation and its implumentations, it will have significant constribution and its influence toward the public service around 15,16%. While a good budget avaibility and its implumentation toward the public service, it will give a significant contribution toward the officer service and its influence around 25 %